Effect of Carboxyl Methyl Cellulose (CMC) Addition on Physicochemical Quality of Salted Egg White Powder - Evanuarini, Herly; Nidhal, Hemas Azizila; Anisa, Cintya Dienardila (Fakultas Peternakan, Universitas Padjadjaran, 2025)
Duck eggs which are processed into salted eggs by the salting method have various advantages, but it cannot be stored for a long time. Efforts that can be made to increase shelf life, improve characteristics, and increase nutritional content include making salted egg whites in the form of powder. Egg powder can be made by drying using an oven, so a stabilizer is needed to reduce damage due to heating. Carboxyl Methyl Cellulose (CMC) is a stabilizer that can be used because it has good hydrophilic properties. The research objective was to improve the physicochemical quality and nutritional content of salted egg white powder (SEWP) so that it can be used as a form of functional food diversification. The research method used a laboratory experiment with a completely randomized design with 4 treatments and 5 replications. The research material is salted egg white and CMC according to the treatment of 2%, 4%,6%, and control. The addition of CMC to salted egg white powder had a very significant (P<0.01) effect on physicochemical quality and also had a significant effect (P<0.05) on the pH value. Based on the research results, 6% CMC added to egg white powder can improve the physicochemical characteristics.